The Influence of Macroeconomic Factors on the Exchange Rate - Tsinta Hayatin Nafisah; Diah Wahyuningsih (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
The exchange rate is a relatively important economic indicator because it influences a country's economy. This study aims to analyze the influence of economic factors, including the inflation rate, money supply, and exports, on the rupiah exchange rate in the long and short term. This study uses monthly data from 2016 to 2021. The analysis tool used is the Error Correction Model. The results indicate that inflation and exports have a positive and significant impact on the rupiah exchange rate in both the long and short terms. Meanwhile, the money supply variable has a positive but insignificant effect on the rupiah exchange rate in the long and short term. Keywords: inflation, money supply, exports, exchange rate, error correction model